TANGGUNG JAWAB PELAKU USAHA KLINIK KECANTIKAN TERHADAP KONSUMEN YANG TIDAK COCOK DENGAN PRODUK KECANTIKAN - Ratna Dewi Damayanti, Putu; Puspawati, I Gst Ayu; Sutama, Ida Bagus Putu (Kertha Semaya : Journal Ilmu Hukum, 2014)
Various attempts to grow beauty clinics in various cities in Indonesia. The rapid growth of the beauty clinic turns out there is a downside, the growth of the business is not accompanied by satisfactory service for consumers, including many consumers who did not match with beauty products issued by the beauty clinic. When experiencing complications in the use beauty clinic business operators who have provided care to the consumer shall be responsible for any losses incurred. Compensation can be either a refund or replacement of goods and / or services that are similar or equivalent value, or health care, or the provision of compensation in accordance with the statutory provisions in force, contained in Article 19, paragraph 1, 2 UUPK . And if consumers can lose legal remedy through litigation and non- litigation means , but in reality many consumers to take legal actions in non- litigation that is returned to the clinic to consult a beauty to be liable for losses suffered by consumers.
Keywords: Beauty Clinic, Responsibilities, Business Communities, Consumers